Case Study—Copanor, Brazil - Dos Santos Rocha, Wilson (Washington, DC: World Bank, 2017)
In 2006, the government of Minas Gerais decided toimplement a bold investment program to make water and sanitation universally accessible in the rural and poorest region of the state. These areas had been leftaside by the state water supply and sanitation (WSS) company, COPASA (Companhia de Saneamento),which had predominantly focused on urban access to WSS services. To do so, the government conducted astudy entitled Project Vida no Vale (VNV, or Life in theValley) that surveyed 1,852 rural localities. Based onthe Project VNV recommendations, the government of Minas Gerais created COPANOR (Copasa Serviços deSaneamento Integrado do Norte e Nordeste de Minas Gerais), a public company, a subsidiary of COPASA,which would be specifically in charge of WSS operationsin rural communities. However, despite the achievements of COPANOR, it has not yet reached financial sustainability, which puts the aggregation model at risk. The state government was prompted to create COPANOR for two main reasons. First, the state company COPASA resisted serving small localities, as doing so could affect its overall sustainability and potentially affect its capacity to deliver good-quality services to its existing customers. Second, several previous experiences of service delivery in ruralareas had failed. However, the 2006 diagnosis found that many of the WSS systemsfunded by PPNSR had been poorly maintained and were dysfunctional. Hence, it became clear to the state government that the PPNSR model should notbe repeated and that an alternative model to deliver WSS service in rural areas should be implemented. The purposes of the COPANOR aggregation encompass professionalization and performance enhancement aswell as economic efficiency.COPANOR also enabled the use of economies ofscale when purchasing treatment products. However,despite those achievements, some progress still needs to be made as water macro metering is not availableand there are no indicators for losses or unaccounted-for water.